الثابت والمتغير في آليات الرقابة البرلمانية في ظل التعديل الدستوري الجزائري لسنة 2016 ودستور المغرب لسنة 2011 - خدوجة, خلوفي (University of Eloued جامعة الوادي, 2020)
يدة الرامية إلى تعديل الدساتير في إطار ظرفية دولية سمتها الأساسية الثورة الاجتماعية التي تقودها الشعوب العربية من أجل إقامة دولة الحق والقانون، قائمة علىّتمكين كل مؤسسة من القيام بمهامها في إطار الاستقلالية والشفافية.وّلعلنصيب المغرب من الوضع الدولي الراهن ّ جاء بإصلاحات كرّسها المؤسس الدستوري كإصدار دستور2011، على غرار الجزائر التي كان آخر ّ الإصلاحات السياسية التي بدأت من2011بإصدار تعديل الدستور2016الذي كان ينتظر منه الكثير في إعادة التوازن بين المؤسسات؛ّإلا أنه قد أكد على ما جاءت به الدساتير السابقة في تكريس وتعزيز المكانة السامية السلطة التنفيذية رغم وجود رقابة البرلمان عليها المتسمة بالطابع الشكلي.ّ ّ يشكل الاختصاص الرقابي الدعامة الأساسية والركيّزة الأولى لنشوء المؤسسة البرلمانية، بدءا بامتلاكها سلطة الموافقة على البرنامج السياس ي في المغرب،وعلى مخطط عمل الحكومة في الجزائر إلى الرقابة اللاحقة عن طريق آليات عدة عقب بيان السياسة العامة من ملتمس الرقابة وتقديم تنبيه للحكومة في المغرب إلى اللوائح وصولا إلى الرقابة الاستعلامية عن طريق الأسئلة والاستجواب في الجزائر، وعن طريق لجان التحقيق. The new reforms aiming at amending the constitutions within the framework of an international circumstance which are characterized mainly by the social revolution led by the Arab peoples in order to establish the state of right and law, are based on the possibility for each institution to do its tasks within the framework 2016 2011 22511012242372020 of independence and transparency, Morocco's share in the current international situation has perhaps come with reforms enshrined by the Constitutional founder like the publication of the 2011 constitution, similar to Algeria, in which the last political reform started from 2011 with the publication of the constitutional amendment of 2016, was supposed to restore the balance between the institutions, but it highlighted what happened in the previous constitutions in devoting and enhancing the high position of the executive power, Although there is a formal oversight of Parliament. The oversight competence constitutes the main pillar and the first basis of the existence of the parliamentary institution, starting with its possession of authority to approve the political program in Morocco and the work plan of the government in Algeria, until subsequent oversight via several mechanisms after the declaration of the general policy of the applicant of the oversight and giving an alert to the government in Morocco, besides the resolutions and the informative oversight by means of questions and hearings in Algeria, and through commissions of investigation.
مجلد11، عدد1
Keywords: رقابة؛البرلمان؛الحكومة؛ّالوزير الأول؛استقالة.; Oversight; Parliament; Government; Prime Minister; Resignation.